How Do Simulations Affect Career Decision Making? The Case of Model Turkish Diplomacy - Oztig, Lacin Idil (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Simulations are now long-established pedagogical tools in IR programs. Concomitant with this development, scholarly attention has been devoted to the impact of IR simulations on students. Recent research has found evidence to suggest that there is an association between IR simulations and students' aspirations toward political and diplomatic careers. However, despite abundant research, we still have little knowledge about how IR simulations impact students' perceptions of the diplomacy profession in general and the role of universities in this profession specifically. This study aims to fill these gaps by analyzing whether and how students' opinions on the diplomacy profession and the role of universities in building diplomatic skills change after participating in Model Turkish Diplomacy simulations. It particularly focuses on how simulation experiences impact career decision-making processes among IR students. This study used a quasi-experimental design. Via convenience sampling, data was collected through pre- and post-simulation (online) survey questionnaires submitted to undergraduate IR students at Yildiz Technical University who enrolled in the courses The Middle East Society and Politics and Diplomatic Correspondence and volunteered to participate in simulations in the fall semester of 2023-2024.
Keywords: Simulations; IR; Model Turkish diplomacy; diplomatic skills; universities; POLITICS; PEDAGOGY; STUDENTS; Government & Law